POLITIK HUKUM PEMINDAHAN IBUKOTA NEGARA INDONESIA DITINJAU DARI UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Amanda Salsabila; Mexsasai Indra; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The discourse on relocating the State Capital by the President of the Republic of Indonesiafrom Jakarta to East Kalimantan raises many pros and cons. Those who are pro thinkit is necessary to move the national capital to East Kalimantan considering that Jakarta bearstoo heavy a burden as the center of government, business center, financial center, trade centerand service center. Meanwhile, the contenders stated that it was not enough to relocatethe State Capital with the policy of the President as the highest authority in the country. Aclear regulation in the form of a Law must be issued immediately so that the President's discoursehas a clear legal basis. The President's policy without the support of regulations in theform of a Law on this project to relocate the State Capital is not the manifestation of a rule oflaw. On the other hand, in the concept of limiting power, the policy of relocating the StateCapital is deemed necessary to involve elements of other state institutions, especially in termsof legislation and regulationsThis research is a normative juridical research, which is based on legal and statutorymaterials. The approach taken includes a literature approach, namely by studying books andlaws and regulations. The type of data used is the type of premier data, secondary datasources, namely data sources that come from books and other regulations. The theory used inthis research is the theory of political law and the theory of separation of powers.From the results of the research, there are two main points that can be concludedwhere the political law desired by the constitution begins with the goal of the state, namelythe welfare of the public at large, which is contained in the preamble to the 1945 Constitution,especially regarding public participation. So the transfer of the nation's capital is not inaccordance with the goals of the nation and state as stated in the 1945 Constitution. whereMontesquieu divides executive, legislative and judicial powers. Although in principle the authorityis divided, in the formation of a law (uu the capital of the country) it must be based onmutual agreement between the president and the DPR. Meanwhile, the president's unilateralpolicies do not reflect proregative rights as stipulated in the 1945 Constitution and precludethe possibility of public participation. So if the old law has not been revoked / repealed, thelaw is still in effect and the president's policy is null and void because there is no binding legalbasis.Keywords: Law Politics, Rule of Law, Policy, UUD 1945.